The Antarctic Treaty System: future mining faces many mathematical challenges - Anthony Press (2015)
This short paper examines how the Antarctic Treaty and its Protocol on Environmental Protection deal with mineral resource activities and the steps that would be required to lift the current ban on mining in the Antarctic.